2011
DOI: 10.1016/j.ijgo.2011.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hysterectomy versus abdominal hysterectomy for severe pelvic endometriosis

Abstract: Compared with AH, LH was associated with fewer complications. LH should, therefore, be the preferred surgical option for women with severe pelvic endometriosis who require a hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 13 publications
1
30
1
5
Order By: Relevance
“…Surgery is an invasive treatment that can cause even more severe complications than a fibroid itself. Potential short-term complications of surgery include febrile morbidity, blood loss, and organ injuries [9], while possible long-term complications, such as fistula formation, adhesion, and sexual dysfunctions [10], can last for many years, even beyond menopause, when a uterine leiomyoma is no longer a threat to health [3]. Consequently, alternative treatments to surgery for the management of fibroid-related symptoms have been sought and evaluated for years to minimize surgery in patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is an invasive treatment that can cause even more severe complications than a fibroid itself. Potential short-term complications of surgery include febrile morbidity, blood loss, and organ injuries [9], while possible long-term complications, such as fistula formation, adhesion, and sexual dysfunctions [10], can last for many years, even beyond menopause, when a uterine leiomyoma is no longer a threat to health [3]. Consequently, alternative treatments to surgery for the management of fibroid-related symptoms have been sought and evaluated for years to minimize surgery in patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Procedures performed in other large studies have either been abdominal hysterectomies or vaginal hysterectomies [1,7,11]. However, laparoscopic hysterectomy is associated with markedly less morbidity than is abdominal hysterectomy [17–21]. A large proportion of hysterectomies can also be carried out vaginally, with considerable benefits to the patient [22]; however, myomas, adnexal pathologies, pelvic adhesions, and a narrow vagina can present obstacles to the use of this route.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that minimally invasive hysterectomy and staging techniques were a feasible and safe alternative to staging via laparotomy for the surgical treatment of endometrial cancer [1]. The advantages of LH over TAH include decreased blood loss, earlier return of bowel function, fewer wound complications, shorter hospital stay, faster return to normal activities, and improved quality of life [1][2][3][4][5][6]. However, several authors have reported increased vaginal cuff dehiscence rates among patients undergoing LH compared with TAH or vaginal hysterectomies (VHs) [7][8][9][10].…”
Section: Discussmentioning
confidence: 94%